Association of Soil-transmitted Helminth Infection and Micronutrient Malnutrition: A Narrative Review - Masangcay, Daniella U.; Amado, An Jlyka Y.; Bulalas, Azel R.; Ciudadano, Sophia R.; Fernandez, Jane D.; Sastrillo, Stacy M.; Mabaggu, Reymund M. (Asian Journal of Biological and Life Sciences)
Micronutrient malnutrition, mainly iron, Vitamin A, and zinc, affects more than 2 billion people worldwide. One notable cause of this condition is an abnormal digestive function due to parasitic intestinal infections. Since infections with soil-transmitted helminths (STH) are observed in 24% of the world’s population, it contributes to approximately 100 million malnutrition in children globally. The following parasites cause this: Ascaris lumbricoides, Trichuris trichiura, and hookworms Ancylostoma duodenale and Necator americanus. This narrative review aims to synthesize the existing literature on the epidemiology, pathogenesis, and clinical manifestations of micronutrient malnutrition—iron, Vitamin A, and zinc to explain its relationship with STH infections. Research journals and articles were retrieved from PubMed and Google Scholar. Search terms include “helminthiasis or STH infection or soil-transmitted helminth infection,” “malnutrition or nutrition deficiency,” “iron or ferritin or hemoglobin,” “Vitamin A or retinol,” and “zinc.”. STH infections can cause micronutrient malnutrition. The existing relationship between STH and micronutrient malnutrition is a significant burden, mainly in children or pregnant women who reside in rural communities of developing countries. Iron deficiency is the most common micronutrient malnutrition manifested in infected populations, mainly in pregnant women. In contrast, Vitamin A deficiency occurs more often in children than in pregnant women. The least common of all micronutrient malnutrition occurring in STH-infected individuals is zinc deficiency. However, since only a few studies have conducted additional assessments for other possible contributing factors (e.g., diet intake, underlying genetic conditions), further research is needed to elucidate the complex interplay of other determinants and risk factors involved in this health scenario.
Keywords: Iron deficiency; Micronutrient malnutrition; Soil-transmitted helminth; Vitamin A deficiency; Zinc deficiency